Earnings management, corporate governance and expense stickiness - Shuang Xue; Yun Hong (China Journal of Accounting Research, 2016)
Cost and expense stickiness is an important issue in accounting and economics research, and the literature has shown that cost stickiness cannot be separated from managers' motivations. In this paper, we examine the effects that earnings management has on expense stickiness. Defining small positive profits or small earnings increases as earnings management, we observe significant expense stickiness in the non-earnings-management sub-sample, compared with the earnings-management sub-sample. When we divide expenses into R&D, advertising and other general expenses, we find that managers control expenses mainly by decreasing general expenses. We further examine corporate governance's effect on expense stickiness. Using factor analysis, we extract eight main factors and find that good corporate governance reduces expense stickiness. Finally, we investigate the interaction effects of earnings management and corporate governance on expense stickiness. The empirical results show that good corporate governance can further reduce cost stickiness, although its effect is not as strong as that of earnings management.
Keywords: 650; Earnings management; Corporate governance; Expense stickiness; Interaction effect